2008
DOI: 10.1042/bc20070053
|View full text |Cite
|
Sign up to set email alerts
|

Mislocalization of human transcription factor MOK2 in the presence of pathogenic mutations of lamin A/C

Abstract: Background information. hsMOK2 (human MOK2) is a DNA-binding transcriptional repressor. For example, it represses the IRBP (interphotoreceptor retinoid-binding protein) gene by competing with the CRX (cone-rod homeobox protein) transcriptional activator for DNA binding. Previous studies have shown an interaction between hsMOK2 and nuclear lamin A/C. This interaction could be important to explain hsMOK2 ability to repress transcription.Results. In the present study, we have tested whether missense pathogenic mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
0
24
0
1
Order By: Relevance
“…However, recent studies suggest that BAF also functions as transcriptional repressor, where it binds specific promoters [104,105]. The rod domain of human lamins A and C also binds directly to the transcription factor MOK-2 [106], and MOK-2 localization depends on lamins A and C [107]. Human lamin A also binds the SREBP-1 in vitro and this interaction is reduced when lamin A has a mutation in the Ig fold that causes familiar partial lipodystrophy [108].…”
Section: Lamins In Transcription and Splicingmentioning
confidence: 99%
“…However, recent studies suggest that BAF also functions as transcriptional repressor, where it binds specific promoters [104,105]. The rod domain of human lamins A and C also binds directly to the transcription factor MOK-2 [106], and MOK-2 localization depends on lamins A and C [107]. Human lamin A also binds the SREBP-1 in vitro and this interaction is reduced when lamin A has a mutation in the Ig fold that causes familiar partial lipodystrophy [108].…”
Section: Lamins In Transcription and Splicingmentioning
confidence: 99%
“…Mutations within the LMNA (lamin A/C) gene, which cause laminopathies, have recently been reported to result in mislocalization of the DNA-binding transcriptional repressor zinc finger protein 239 (ZNF239, also known as MOK2). The pathogenic lamin A/C mutant protein sequesters ZNF239 into nuclear aggregates, and this process is thought to subsequently deregulate ZNF239 target genes (Dreuillet et al, 2008).…”
Section: Mislocalization Through Changes In Protein Interaction or Momentioning
confidence: 99%
“…Mutations within the LMNA (lamin A/C) gene, which cause laminopathies, have recently been reported to result in mislocalization of the DNA-binding transcriptional repressor zinc finger protein 239 (ZNF239, also known as MOK2). The pathogenic lamin A/C mutant protein sequesters ZNF239 into nuclear aggregates, and this process is thought to subsequently deregulate ZNF239 target genes (Dreuillet et al, 2008).Hereditary genetic changes that alter the post-translational modifications that are relevant for correct protein localizations are also associated with human diseases. In a recent study, Cordeddu et al reported a genetic change in patients with Noonan-like syndrome that introduces an N-myristoylation site in SHOC2, a leucine-rich repeat-containing protein.…”
mentioning
confidence: 99%
“…Crude protein extracts were prepared and purified as described previously (Dreuillet et al 2008). The GST fusion proteins bound to glutathione beads were used as 50% slurry in the appropriate buffer.…”
Section: Preparation Of Recombinant Proteins In E Colimentioning
confidence: 99%